2020
DOI: 10.5194/hess-24-2561-2020
|View full text |Cite
|
Sign up to set email alerts
|

Concentration–discharge relationships vary among hydrological events, reflecting differences in event characteristics

Abstract: Abstract. Studying the response of streamwater chemistry to changes in discharge can provide valuable insights into how catchments store and release water and solutes. Previous studies have determined concentration–discharge (cQ) relationships from long-term, low-frequency data of a wide range of solutes. These analyses, however, provide little insight into the coupling of solute concentrations and flow during individual hydrologic events. Event-scale cQ relationships have rarely been investigated across a wid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 52 publications
5
123
0
Order By: Relevance
“…We found that the event water fractions from two-component hydrograph separation (isotopes) and EMMA (multi-tracer) were comparable (Table 4). Similar to our results, Ladouche et al (2001) found for the 0.8 km 2 Strengbach catchment in France that the hydrograph separation results based on δ 18 O (f pe -10 %) were relatively similar to the results of their mixing analyses (including DOC, Si, Ba and U), and that a multi-tracer approach allowed them to distinguish between pre-event water contributions from the upper and lower part of the catchment. We found that concentrations of metals, such as iron or copper, were much higher than expected from mixing of rainfall and baseflow, whereas weathering-derived solutes, such as sodium or calcium, were lower than expected from mixing of rainfall and baseflow.…”
Section: Which Areas or Sources Contribute To Stormflow?supporting
confidence: 90%
See 1 more Smart Citation
“…We found that the event water fractions from two-component hydrograph separation (isotopes) and EMMA (multi-tracer) were comparable (Table 4). Similar to our results, Ladouche et al (2001) found for the 0.8 km 2 Strengbach catchment in France that the hydrograph separation results based on δ 18 O (f pe -10 %) were relatively similar to the results of their mixing analyses (including DOC, Si, Ba and U), and that a multi-tracer approach allowed them to distinguish between pre-event water contributions from the upper and lower part of the catchment. We found that concentrations of metals, such as iron or copper, were much higher than expected from mixing of rainfall and baseflow, whereas weathering-derived solutes, such as sodium or calcium, were lower than expected from mixing of rainfall and baseflow.…”
Section: Which Areas or Sources Contribute To Stormflow?supporting
confidence: 90%
“…Knowledge of which areas are connected and contribute to streamflow is important because it helps us to shape our conceptual understanding of how catchments function. For example, Ladouche et al (2001) showed for the 0.8 km 2 Strengbach catchment in France that the upper layers of saturated areas contributed up to 30 % of the discharge during the initial stages of a rainfall event, even though these areas occupied only 2 % of the catchment area. However, during the final stage of the event, upslope and downslope areas contributed equally to flow.…”
Section: Introductionmentioning
confidence: 99%
“…While chemodynamic behavior of redox-sensitive and biogeochemically active solutes is commonly observed, chemodynamic behavior of weatheringbased ions has also been reported in some carbonate-dominated catchments (e.g., Sullivan et al, 2018). This is usually attributed to spatial heterogeneity, activation of different flow paths and/or mineral control (Koger et al, 2018;Rose et al, 2018;Molins et al, 2019;Knapp et al, 2020). At PH, sulfuric acid weathering is estimated to account for 35-75% carbonate dissolution (Winnick et al, 2017), thus resulting in source-limitation of weathering solutes at this location.…”
Section: Resultsmentioning
confidence: 96%
“…The log-log plot here indicates that the hypothetical solute shows dilution with increasing discharge at both stations A and B, albeit to different degrees. Although recent availability of highfrequency data sets are expanding the scope and application of these techniques (e.g., Rose et al, 2018;Knapp et al, 2020), log-log plots are typically applied to long time-frame datasets and are used to compare solutes across different catchments, while standard C-Q relationships are typically used to study solutes intensively at one station with temporal differentiation. More importantly, both the standard and logarithmic C-Q relationships provide solute behavior characteristics at a single location within a stream.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Seasonal c-q patterns were found to differ from event-based ones for phosphorus and nitrate in 219 French catchments covering a wide range of soil, climate and land use characteristics (Minaudo et al, 2019). These differences between long-term and event-based c-q responses likely indicate different controls on solute transport and storage processes on different temporal scales (Knapp et al, 2020). More recently, the notion that biogeochemical cycling is switched off or severely dampened, depending on the magnitude of the storm event has gained prominence, with higher magnitude storm events thought to have a greater damping effect (Bernhardt et al, 2018;Raymond et al, 2016) compared to low-magnitude storm events that can preserve diel cycles (Burns et al, 2016).…”
Section: Introductionmentioning
confidence: 92%